Straightforward synthesis of alpha,beta-epoxysilanes from terminal epoxides by lithium 2,2,6,6-tetramethylpiperidide-mediated deprotonation-in situ silylation - Hodgson, D; Reynolds, N; Coote, S (2002)
Lithiation-in situ silylation of simple terminal epoxides using lithium 2,2,6,6-tetramethylpiperidide in combination with trimethylsilyl chloride provides a direct and experimentally convenient process for the synthesis of trans-α,β-epoxysilanes. © 2002 Elsevier Science Ltd. All rights reserved.